1994
DOI: 10.1007/bf01541562
|View full text |Cite
|
Sign up to set email alerts
|

Family affiliation and prostitution in a cultural context: Career onsets of Taiwanese prostitutes

Abstract: American researchers emphasize family disaffiliation resulting from negative experiences as an important career contingency for prostitutes. They suggest that cohesive families insulate daughters from entering prostitution, an implication that ignores cultural variations within the United States and worldwide. This study examined the nature of family affiliations among prostitutes in Taiwan, a nation characterized by strong family cohesion and widespread prostitution. The traditional status and role of daughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…The fact that a family member mediated the first contact with the sex business to the respondent is not rare at all, as Demleitner (13) states. At the same time, for example according to the findings of Taiwan police, a half of the woman approached entered sex business due to pressure from the family (14). The women also often support their family financially through sex work (15), which was stated by some respondents in our study too.…”
Section: Discussionmentioning
confidence: 62%
“…The fact that a family member mediated the first contact with the sex business to the respondent is not rare at all, as Demleitner (13) states. At the same time, for example according to the findings of Taiwan police, a half of the woman approached entered sex business due to pressure from the family (14). The women also often support their family financially through sex work (15), which was stated by some respondents in our study too.…”
Section: Discussionmentioning
confidence: 62%
“…Two more aspects of identity formation specifically in relation to Taiwanese culture deserve consideration. Research on American prostitution “has consistently emphasized the importance of family disaffiliation as a career contingency” (McCaghy & Hou, 1994). Likewise, the majority of prostituted juveniles in Taiwan have run away from their families.…”
Section: Discussionmentioning
confidence: 99%
“…The scarce research that exists has often focused on the rural-urban migration patterns of women who enter prostitution as a result of economic motivations (McCaghy & Hou, 1994;Mensendiek, 1997;Phongpaichit, 1982). For instance, researchers found that women who migrated to cities from rural areas of Thailand and entered prostitution reported social (matrilineal family structure), economic, and environmental factors (loss of land and resettlement) as motivations for their migration (Mensendiek, 1997).…”
Section: Contextual and Environmental Factorsmentioning
confidence: 99%